Personality and cognition: shoal size discrimination performance is related to boldness and sociability among ten freshwater fish species - Shi-Jian Fu; Na Zhang; Jie Fan (Animal Cognition)
Abstract Several studies have reported that animals’ personalities are often correlated with individual differences in cognition. Here, we tested whether personality is related to cognition across species, focusing on 10 freshwater fishes and a task relevant for fitness, the ability to discriminate shoal size. Bolder species exhibited more ‘shuttle’ behavior for information sampling during shoal selection and showed high performance (HP) in the numerical discrimination than shyer species, i.e., low performance (LP) species. Species at both the high and low ends of sociability showed LP, possibly due to loosened selection pressure because of either no need to perform shoal size discrimination tasks frequently in nature for very high sociability species or decreased willingness and motivation to join and stay within shoals for very low sociability species. Notably, the numerical discrimination was sensitive to the numerical contrast ratio in LP species but not in HP species, suggesting that the numerical system used for size discrimination also varied between species. Overall, we demonstrated the interspecies relationship between personality and shoal size discrimination across fish species, suggesting an evolutionary link between numerical abilities and behavior.